The Impact of Digital Financial Literacy on the Adoption of QR Codes and Mobile Money, and Its Effect on SME Performance in Central Kalimantan - Sarlawa, Rita; Azis, Akbar (MANDAR: Management Development and Applied Research Journal, 2025)
This study investigates the influence of Digital Financial Literacy (DFL) and Transaction Cost Burden (TCB) on the adoption of QR Code and Mobile Money payment systems, as well as their subsequent impact on the performance of Small and Medium-sized Enterprises (SMEs). Utilizing a quantitative methodology and Generalized Structured Component Analysis (GSCA), data were collected from a sample of 300 SMEs in Central Kalimantan that have either adopted or are in the process of adopting digital payment technologies. The results indicate that DFL significantly facilitates the adoption of QR Code systems, whereas TCB also influences adoption, suggesting that cost factors affect but do not entirely inhibit digital adoption. Moreover, the adoption of QR Code systems notably promotes the use of Mobile Money, with both systems positively affecting SME performance by enhancing transaction efficiency and financial management. Digital Financial Literacy indirectly contributes to improved performance through these adoption pathways, while TCB moderates the relationship between adoption and outcomes. These findings extend the Technology Acceptance Model (TAM) by incorporating literacy and cost considerations, offering new perspectives on the acceptance of digital payments among SMEs. In practice, the study advocates enhancing digital financial literacy initiatives and reducing transaction-cost barriers to promote inclusive digital transformation and sustainable growth of SMEs in emerging economies